Changes in clinical and biochemical characteristics in combination treatment for diabetic macular edema (Ukrainian Journal of Ophthalmology, 2025)
Background: Diabetic macular edema (DME) can be seen in both types of diabetic retinopathy (DR), and is a major cause of vision loss.Purpose: To evaluate the efficacy of the combination treatment for DME in type 2 diabetic patients with non-proliferative diabetic retinopathy (NPDR). Material and Methods: An open-label, controlled study included 45 type 2 diabetic patients with both NPDR and DME. Patients of the aflibercept-plus-hyperbaric oxygen (HBO) group and those of the aflibercept-only (control) group received a monthly intravitreous aflibercept at a dose of 2 mg (50 µL) for 3 months. In addition, the former patients received an adjunctive treatment with ten sessions of HBO in the period between the first and the third injections. Changes in clinical and biochemical characteristics were assessed at 3 months after initiation of treatment.Results: At 3 months, patients of the aflibercept-plus-HBO group showed a statistically significant improvement in visual acuity, improvement in retinal light sensitivity, reduction in manifestations of DME, and statistically significant reductions in blood glucose and glycated hemoglobin levels. At 3 months, the changes in the activities of antioxidant enzymes were more substantial in this group, and these improvements were statistically significant compared to baseline and compared to controls. Particularly, superoxide dismutase (SOD) activity, catalase (CAT) activity, and glutathione reductase (GSR) activity decreased by 33.9%, 22.4% and 17.7%, respectively, compared to baseline, and 34.78%, 28.9%, and 25.3%, respectively, compared to controls.Conclusion: Treatment for DME with the use of aflibercept and adjunctive HBO caused a substantial reduction in the frequency of DME and improvements in visual acuity and retinal light sensitivity in type 2 diabetic patients NPDR. Under these conditions, a decrease in the activity of CAT was larger than that of GSR but smaller than that of SOD, likely indicating an improvement in antioxidant protection.
Keywords: diabetic macular edema; aflibercept; hyperbaric oxygen therapy; enzymes